Nyanyian Sunyi: Pengarsipan Budaya Baandi-Andi dan Bahasa Dayak Meratus - Ramadhan, Akhmad David; Hamid, Ismar; Ramadhan, Ahmad; Thiansyah, Adhera Nur; Yahya, Nur Azima; Putri, Maziatul; Rahmawati; Lisdawanti; Nadiba, Shaffa; Abdan, Indra Suci; Hamdi, Resyda Syaibatul; Azzahra, Shamiyah Noor; Hariadi (Prodi Sosiologi FISIP ULM, 2024)
This community service program focuses specifically on Baandi-Andi culture and Dayak Meratus language which are threatened to be lost by modernization and social change through a series of activities. Therefore, this program is present as a step in the struggle against cultural diffusion in the Dayak Meratus community. The story archive in Baandi-andi culture includes in-depth interviews, transcripts of interview results, and story narration. Dayak Meratus language archives include vocabulary interviews, live-ins, school assignments, and alphabetizing. The data obtained was then validated through Forum Group Discussion (FGD). This program was implemented in Datar Ajab Village, Hantakan District, Hulu Sungai Tengah Regency. Data was obtained from interviews with resource persons who were considered adequate and mastered the issues that would be the focus of this program. The community service team managed to gather the community's views on the sustainability of their culture. The discussion involved villagers, village officials, and community leaders to identify the most threatened cultures and find solutions for their preservation. The results of this program include the collection of more than 500 vocabularies of the Dayak Meratus language and their meanings, as well as a draft collection of folklores that are an integral part of the Baandi-andi culture. With an archive that can be accessed by the wider community, it is hoped that the wider community can recognize and appreciate the richness of Dayak Meratus culture, and encourage participation in its preservation. The conclusion of this research confirms that the condition of Baandi-andi culture and Dayak Meratus language is increasingly eroded by the times. Therefore, there is a need for strong awareness and concrete actions to preserve the existing cultural heritage.